Protective Effects of Dimethyl-Fumarate Against Doxorubicin-induced Cardiac Injury in Rats - Sara A. Al-Kenany; Nada N. Al-Shawi (Iraqi Journal of Pharmaceutical Sciences, 2024)
Doxorubicin is a wide-range antineoplastic agent; nonetheless, doxorubicin’s related cardiotoxic adverse effect that is mediated via oxidative damage restricts clinical use. Dimethyl-Fumarate an agent to manage multiple sclerosis exhibited an anti-oxidant, and anti-inflammatory activity by stimulating Nrf-2-pathway. The current investigation was developed to examine how likely DMF protect against Dox-related cardiac injury in rats. Males and females Wistar rats treated by DMF-only (15 mg/kg /day)for 14 days orally or before DOX IP-inj. at (15mg– single-dose on day 14) to prompt cardiac injury. Results revealed that DMF considerably alleviated DOX-related cardiotoxicity, by decreasing CK-MB and LDH serum concentrations & ameliorated histological alterations. Also, there was a significant inhibition in cardiac OS thru reducing MDA-level, increasing GSH, SOD, CAT and Gpx-1; upregulated Nrf2 protein and gene level, promoting HO_1 gene plus protein synthesis, reduced Keap1 and NF-kB genes expression; furthermore, DMF reduced TNF-a, IL-1b signiﬁcantly, and suppressed apoptotic cell death. In conclusion, the current study established that DMF alleviated the cardiac injury stimulated by DOX via modulating apoptotic responses and reaction to oxidants by stimulating Nrf-2; suggesting that DMF might be used as a possible chemotherapeutic-adjuvant to improve anthracyclines-related cardiotoxicity.